The supply of inorganic fertilizers to smallholder farmers in Uganda: Evidence for Fertilizer Policy Development - Benson, Todd; Lubega, Patrick; Bayite-Kasule, Stephen; Mogues, Tewodaj; Nyachwo, Julian (International Food Policy Research Institute, 2012)
Inorganic fertilizer is one of a handful of agricultural technologies that has immense potential for raising the productivity of poor smallholder farmers, enabling them to increase income, accumulate assets, and set themselves economically on a pathway out of poverty. The very low prevalence of fertilizer use by Ugandan farmers—well below 5 percent—is evidence that farmers find it difficult to access fertilizers for their crops at a price that will allow them to obtain sufficient and reliable returns from their investment in fertilizer.